2014
DOI: 10.4103/2278-330x.126516
|View full text |Cite
|
Sign up to set email alerts
|

Gestational trophoblastic neoplasia: A 6 year retrospective study

Abstract: Aims and Objectives:To study the clinical presentations of gestational trophoblastic neoplasia and its response to chemotherapy.Materials and Methods:This is a retrospective study of 28 women of gestational trophoblastic neoplasia evaluated over a period of 6 years from January 2004 to December 2009. Patients were evaluated on the basis of their age, number of deliveries, history of abortion or molar pregnancy, and the treatment received. All patients were scored on the basis of WHO scoring system. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 8 publications
5
12
2
Order By: Relevance
“…Two high risk GTN patients treated with EMA-CO achieved remission with four and eight cycles of chemotherapy each. This is comparable with a study conducted by Shivastava et al 19 where the low risk patients treated with MTX achieved remission after one cycle, those who were treated with Act-D achieved remission after three cycles and in high risk patients treated with EMA-CO, ten patients achieved remission after three cycles and six patients achieved remission after six cycles.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Two high risk GTN patients treated with EMA-CO achieved remission with four and eight cycles of chemotherapy each. This is comparable with a study conducted by Shivastava et al 19 where the low risk patients treated with MTX achieved remission after one cycle, those who were treated with Act-D achieved remission after three cycles and in high risk patients treated with EMA-CO, ten patients achieved remission after three cycles and six patients achieved remission after six cycles.…”
Section: Discussionsupporting
confidence: 78%
“…However, different studies reported 71% (Escobar et al), 27 87.7% (Bafna et al) 28 and 89.4% (Shrivastava et al) 19 which could be due to the presence of widespread metastatic disease in their patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Transvaginal sonogram and sonohysterography examination were also performed, however the results were unremarkable. Following a consultation, gestational choriocarcinoma with pulmonary and cerebral metastasis [FIGO stage IV; World Health Organization score, 15 (8)] was diagnosed, which had been misdiagnosed as pulmonary tuberculosis previously at the local hospital. After written informed consent was obtained, systemic multi-agent chemotherapy was administered (Table I).…”
Section: Case Reportmentioning
confidence: 99%